Detection of mercury(II) by DNA templated gold nanoclusters based on forming thymidine–Hg2+–thymidine duplexes. (22nd October 2014) - Zhu, Shanshan; Zhuo, Yan; Miao, Hong; Zhong, Dan; Yang, Xiaoming
Abstract We have successfully synthesized gold nanoclusters (AuNCs) templated with DNA (5′‐CCCCCCCCCCCCTTTTTT‐3′), and subsequently employed the fluorescent DNA‐AuNCs as a novel probe for sensitive detections of mercury ions (Hg2+). Basically, the procedure is due to the formation of thymidine–Hg2+–thymidine duplexes between DNA‐AuNCs and Hg2+, thus leading to aggregations of DNA‐AuNCs described here occurring, and facilitating their fluorescence decrease. Significantly, this decrease of fluorescent signals permitted sensitive detection of Hg2+ in a linear range of 0.1–100 µmol L−1, with a detection limit of 0.083 µmol L−1 at a signal‐to‐noise ratio of 3. Additionally, the practicality of this probe for assaying Hg2+ in human urine and lake water samples was further validated, and showed various advantages including simplicity, selectivity, sensitivity and low cost, demonstrating its potential to broaden ways for assaying Hg2+ in real samples. Copyright © 2014 John Wiley & Sons, Ltd.